The 100 - Morgan, Kass. (London : Hodder & Stoughton, 2013)
When one hundred juvenile delinquents are sent on a mission to recolonize Earth, they get a second chance at freedom, friendship, and love, as they fight to survive in a dangerous new world.
Young Adult.
Young Adult
Keywords: Juvenile delinquents -- Juvenile fiction; Survival -- Juvenile fiction; Juvenile delinquents -- Fiction; Science fiction; Survival -- Fiction; Juvenile delinquency -- Fiction; Science fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Science fiction